2007
DOI: 10.1063/1.2717532
|View full text |Cite
|
Sign up to set email alerts
|

Improving spatial resolution of two-photon microfabrication by using photoinitiator with high initiating efficiency

Abstract: The lateral spatial resolution (LSR) in two-photon induced polymerization was improved to 80nm by using an anthracene derivative (9,10-bis-pentyloxy-2,7-bis[2-(4-dimethylamino-phenyl)-vinyl]anthracene (BPDPA)) as a highly sensitive and efficient photoinitiator. Photocurable resin containing 0.18mol% BPDPA exhibited a low polymerization threshold of 0.64mW at 800nm. Theoretical calculations showed that the LSR can be increased by reducing the laser power, indicating that the LSR could be improved using more sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(140 citation statements)
references
References 12 publications
2
137
0
1
Order By: Relevance
“…We find that increasing the photoresist sensitivity does not increase the resolution (contradicting Ref. [6]) but only increases the dynamic range. For low repetition rates, the sensitization even decreases the resolution, as it decreases the non-linearity of the process towards N = 2.…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…We find that increasing the photoresist sensitivity does not increase the resolution (contradicting Ref. [6]) but only increases the dynamic range. For low repetition rates, the sensitization even decreases the resolution, as it decreases the non-linearity of the process towards N = 2.…”
Section: Resultsmentioning
confidence: 39%
“…From the very beginning [2], DLW has been used to produce sub-wavelength feature sizes. During the last decade, the impact of several experimental parameters has been examined in order to increase the photoresists' resolution [5,6,7,8,9]. While improved feature sizes have been demonstrated using a photoresist with higher sensitivity [6] other results have indicated that completely unsensitized photoresists offer the smallest features [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Femtosecond lasers are frequently used to create 3D patterns in polymers and glasses. [3][4][5][6][7] However, 3D metal direct-writing remains a challenge. Here, we describe a method to fabricate silver nanostructures embedded inside a polymer matrix using a femtosecond laser centered at 800 nm.…”
Section: Introductionmentioning
confidence: 99%
“…As the majority of the materials are bio-compatible [16,17], this approach was employed for the manufacturing of artificial scaffolds for cell proliferation studies [18,19], medical implants for tissue engineering [20,21] as well as regenerative medicine [22,23]. In all of the mentioned examples the materials were passive polymers sensitized only with a photoinitiator responsible for the efficient photostructuring [24]. In order to increase the functionality of the microstructures and metamorphose them into operating devices additional doping with optically active [25,26], magnetic [27,28], and biological [29,30] ingredients has been applied.…”
Section: Introductionmentioning
confidence: 99%